Beginning C - From Beginner to Pro (6th Edition) - Gonzalez-Morris, German; Horton, Ivor (Apress, an imprint of Springer Nature, 2020)
Learn how to program using C, beginning from first principles and progressing through step-by-step examples to become a competent, C-language programmer. All you need are this book and any of the widely available C compilers, and you'll soon be writing real C programs. You'll discover that C is a foundation language that every programmer ought to know. Beginning C is written by renowned author and expert programme. This book increases your programming expertise by guiding you through the development of fully working C applications that use what you've learned in a practical context. You'll also be able to strike out on your own by trying the exercises included at the end of each chapter. At the end of the book you'll be confident in your skills with all facets of the widely-used and powerful C language.